Arts on Prescription in Scandinavia: a review of current practice and future possibilities - Jensen, A.; Stickley, Theodore; Torrisen, W.; Stigmar, K. (SAGE, 2016)
Aims: This article reviews current practice relating to arts and culture on prescription in Sweden, Norway, Denmark and in the UK. It considers future possibilities and considers each of the Scandinavian countries from a culture and health policy and research perspective. The UK perhaps leads the field of Arts on Prescription practice and subsequent research is described in order to help identify what the Scandinavian countries might learn from the UK research. Method: The method adopted for the literature search, was a rapid review which included peer-reviewed and grey literature in English and the respective languages of Scandinavia. Results: The discussion considers the evidence to support social prescription and the obstacles of the implementation of Arts on Prescription in Scandinavian countries. Conclusion: The article concludes that of the Scandinavian countries, Sweden is ahead in terms of Arts on Prescription and has embraced the use of culture for health benefits on a different scale compared to Norway and Denmark. Denmark, in particular is behind in recognising ways in which art and culture can benefit patients and for wider public health promotion. All three countries may benefit from the evidence provided by UK researchers.